Influence of Cooling Process Routes after Intercritical Annealing on Impact Toughness of Duplex Type Medium Mn Steel - Koh-ichi Sugimoto; Hikaru Tanino (Metals, 2021)
To apply the duplex type low-carbon medium-manganese steel to the hot/warm-forging and -stamping products, the influence of cooling process routes immediately after intercritical annealing such as air-cooling (AC) and isothermal transformation (IT) processes on the impact toughness of 0.2%C-1.5%Si-5%Mn (in mass %) duplex type medium-Mn (D-MMn) steel was investigated. Moreover the microstructural and tensile properties were also investigated. The AC process increased the volume fraction of reverted austenite but decreased the thermal and mechanical stability in the D-MMn steel, compared to the IT process. The AC process increased the tensile strength but decreased the total elongation. The Charpy V-notch impact value and ductile-brittle transition temperature were deteriorated by the AC process, compared to the IT process. This deterioration of the impact toughness was mainly related to the reverted austenite characteristics and fracture mode.